2012
DOI: 10.17925/enr.2013.08.01.46
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Hyperactivity and Sympathovagal Imbalance in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder with progressive loss of upper and lower motor neurons. Autonomic nervous abnormalities, including sympathetic hyperactivity and sympathovagal imbalance, have been found in both early and advanced stages of ALS. In early stage, the dysfunction may be subclinical. Occasionally, elevated blood pressure or heart rate and increased sweating may be observed. In advanced stage when ventilators are required, the sympathetic hyperactivity may lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 18 publications
0
25
0
4
Order By: Relevance
“…Although Hannuksela et al have reported the risks of sauna bathing, only one case report in Japanese on nonexertional heatstroke during a bedrock bath exists . Our case demonstrated that falling asleep in a bedrock bath might cause central sympathetic hyperactivity, which sometimes results in sudden death as a result of circulatory collapse …”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Although Hannuksela et al have reported the risks of sauna bathing, only one case report in Japanese on nonexertional heatstroke during a bedrock bath exists . Our case demonstrated that falling asleep in a bedrock bath might cause central sympathetic hyperactivity, which sometimes results in sudden death as a result of circulatory collapse …”
Section: Discussionmentioning
confidence: 63%
“…Her vital signs showed hypertensive crisis without counter‐regulation of heart rate, followed by the consecutive circulatory collapse every 2 hours, shown in Figure B. It was similar to “autonomic storm” found in amyotrophic lateral sclerosis, suggesting that limbic system may have been involved . The fluctuating blood pressure probably due to central sympathetic hyperactivity quitted on hospital day 5 without life‐threatening events.…”
Section: Case Reportmentioning
confidence: 70%
“…Unstable blood pressure occasionally results in circulatory collapse and sudden death . Particularly, paroxysmal hypertensive attacks and subsequent nocturnal hypotension have been reported in ALS patients with TIV, and disease‐specific central sympathetic hyperactivity, sympathovagal imbalance, and secondary down‐regulation of peripheral alpha‐noradrenergic receptors might play a key role in these vasomotor symptoms . These vasomotor features may be similar to autonomic dysreflexia and central sympathetic de‐efferentation signs in cervical spinal cord injuries, but those in ALS are of a different pathophysiology, in which the central sympathetic tone is hyperactive.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ALS living with TIV often display non‐motor clinical manifestations over a long disease course, including macroglossia, autonomic dysfunction, glucose intolerance or hyperglycemia, infection, gall bladder or urinary stones, and decubitus ulcers . These may affect the quality of life and survival time of patients; however, their prevalence is unknown.…”
mentioning
confidence: 99%
“…Further studies may be required to show the pathognomonic importance of autonomic dysfunction in ALS [8]. …”
Section: Discussionmentioning
confidence: 99%